Water in Protic Ionic Liquids: Properties and Use of a New Class of Electrolytes for Energy‐Storage Devices. Issue 16 (17th July 2019) - Stettner, Timo; Gehrke, Sascha; Ray, Promit; Kirchner, Barbara; Balducci, Andrea
Abstract: In this work, the properties of "water‐in‐PIL" (PIL=protic ionic liquid) electrolytes are reported based on 1‐butylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PyrH4 TFSI). Taking advantage of experimental and theoretical investigations, it is shown that the amount of water inside the electrolyte has a dramatic effect on the viscosity, conductivity, density, cation–anion interplay, and electrochemical stability of PyrH4 TFSI. The impact of water on the properties of this ionic liquid also affects its use as an electrolyte for electrochemical double‐layer capacitors (EDLCs). It is shown that the presence of water improves the transport properties of PyrH4 TFSI, with a beneficial effect on the capacitance retention of the devices in which these electrolytes are used. However, at the same time, water reduces the operative voltage of EDLCs containing this PIL as the electrolyte and, furthermore, it has a strong impact on the inactive components of these systems. To suppress this latter problem, and to realize EDLCs with high stability, the use of inactive components stable in aqueous environment appears necessary. Abstract : Benefitting from water : The properties of protic ionic liquids (PILs) can be tuned by the addition of water. The addition of water improves the transport properties of these ionic liquids and, utilizing appropriate inactive components, allows the realization of electrochemical double‐layer capacitors with promising performance. On the basis of these results, water‐in‐PILs can be considered as new and interesting class of electrolytes for energy‐storage devices.